On Multivalued Hybrid Contractions with Applications. (11th July 2020) - Alansari, Monairah; Mohammed, Shehu Shagari; Azam, Akbar; Hussain, Nawab
Abstract : Recently, a notion of b -hybrid contraction for single-valued mappings in the framework of b -metric spaces which unify and improve several significant existing results in the corresponding literature was introduced. This paper presents a multivalued generalization for such contraction. Moreover, one of our obtained results is applied to analyze some solvability conditions of Fredholm-type integral inclusions. Nontrivial examples are also provided to support the assertions of our theorems.